2002
DOI: 10.1243/135065002760364831
|View full text |Cite
|
Sign up to set email alerts
|

A study of a journal bearing lubricated by couple stress fluids considering thermal and cavitation effects

Abstract: A theoretical study of a ®nite grooved journal bearing lubricated with couple stress¯uids is made considering both thermal and cavitation effects. On the basis of the Stokes couple stress¯uid model, the modi®ed Reynolds equation and the energy equation are derived and then numerically solved together with the heat conduction equation. The solution to the modi®ed R eynolds equation is determined using the Elrod cavitation algorithm. The effects of couple stress on the performance of a journal bearing are invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…For validation of simulated results from developed code in Fortran77, the comparison of computed fluid film reaction   o F in kN is made with results by Wang et al [15] for bearing operates under couple stress and Newtonian lubricants as shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For validation of simulated results from developed code in Fortran77, the comparison of computed fluid film reaction   o F in kN is made with results by Wang et al [15] for bearing operates under couple stress and Newtonian lubricants as shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to different computational methods, a maximum deviation of 2-4% of present results with the published results has been observed. A finite difference method was used by Wang et al [15] in their study while finite element method has been applied in current study Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elsharkawy et al [14] investigated a solution for a hydrodynamics FJB operating with CSF to evaluate the parameter of the couple stress and eccentricity ratio for a known pressure field measured from the experimental test. Wang et al [15] studied numerically a thermo-hydrodynamic lubrication for FJB operating with CSF dependent on the Stokes couple stress lubricant theory and taking into account the cavitation effect. They used the ECA in the solution of the modified Reynolds equation.…”
Section: Introductionmentioning
confidence: 99%
“…• Include the rheological properties of the lubricant, such as variations of viscosity with temperature, pressure and shear stress and of density with pressure. Also, the dissipated energy by viscous effects can be important ( [114]) and the Elrod-Adams equation should be solved coupled with the energy equation.…”
Section: Future Workmentioning
confidence: 99%